AUTHENTIC MATERIALS: EFFECTIVE SOLUTIONS FOR LISTENING IN EFL CONTEXT - Fitria Aprilia (HOLISTICS, 2016)
Listening was previously considered as passive skill but now that assumption has been neglected. Lack of adequate exposure to listening and dearth of attention with regard to these issues sets the ground for authentic listening materials to fill the gaps in EFL context. Authentic materials – unsolicited, spontaneous,  natural and covering a wide spectrum of styles from formal to very informal, can truthfully reflect the real life language, narrow the distance between the learners and the target language used in reality, it becomes increasingly attractive to language experts, classroom practitioners and the learners. The fundamental purpose of this paper is to present the power of authentic materials as effective solutions for listening ability in students of English as a foreign language. The authentic materials could be a great help in reaching the goal of improving listening skill and is going to be discussed in greater detail in this paper.